Plac1 promotes nasopharyngeal carcinoma cells proliferation, migration and invasion via Furin/NICD/PTEN pathway. (April 2021) - Lin, Chuanbao; Qian, Pengfei; Zhang, Yan; Liu, Zhihui; Dai, Kun; Sun, Dawei
Highlights: Plac1 and Furin/NICD/PTEN pathway were involved in NPC. Plac1 had an interaction with Furin. Plac1 promoted NPC progression via Furin/NICD/PTEN pathway. Abstract: Placenta-specific protein 1 (Plac1) has critical functions in multiple human malignancies, but its role in nasopharyngeal carcinoma (NPC) was unclear. Clinical samples of NPC and adjacent normal tissue were collected. Plac1 expressions in both tissues and cells were measured. After cell transfection, NPC cell viability, proliferation, migration and invasion were detected using cell counting kit-8 (CCK-8) assay, colony formation assay, scratch assay and Transwell assay. Relative expressions of Plac1 and proteins related to migration and invasion (E-Cadherin, N-cadherin, Matrix metalloproteinase2 (MMP2), and MMP9), Furin/Notch1 intracellular domain (NICD)/phosphate and tension homology (PTEN) pathway (NICD, PTEN, phosphorylated-Akt (p-Akt), Akt) were quantified by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot as needed. The interaction between Plac1 and Furin, a member of Furin/NICD/PTEN Pathway, was analyzed using co-Immunoprecipitation (co-IP) assay. Plac1 expression was upregulated in both NPC tissue and cells. Overexpressed Plac1 promoted Plac1 and Furin expressions and increased cell viability, proliferation, migration and invasion of NPC cells, while silencing Plac1 showed the opposite effects. Plac1 interacted with Furin, overexpression of Furin reversed the inhibitory effects of silencing Plac1 on NPC cell proliferation, migration, and invasion, and also reversed the effects of silencing Plac1 on Furin/NICD/PTEN pathway-, cell migration-, and invasion-related protein expressions. Plac1 promoted NPC cell proliferation, migration and invasion via Furin/NICD/PTEN Pathway. The findings of this study provide a possible therapeutic method for NPC treatment.